Pelaksanaan Pemeliharaan Terminal Bus Tipe B di Jakarta Timur - M. Agphin Ramadhan; Prihantono Prihantono; Sarry Diyah Pangesti (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2022)
This study aims to identify the level of suitability of maintenance at Type B Bus Stations in East Jakarta based on Standard Operating Procedures (SOP), and to identify the Budget Estimate Plan for repair work at the three station. The object of this research is Rawamangun, Klender and Pinang Ranti Bus Stations. The data collection was carried out by preliminary observation, documentation and observation using a checklist table. The research method used is quantitative with a descriptive approach to describe the object under study and the research result. The results showed average suitability between the SOP of the bus stations and the maintenance showed an average of 79.52% (Rawamangun), 66.68% (Klender), and 61.46% (Pinang Ranti). Then the results of the calculation of the Budget Estimate Plan that are Rp. 11,185,125.73 (Rawamangun), Rp. 16,773,795.08 (Klender), and Rp. 16,852,275.49 (Pinang Ranti). It can be concluded that the building maintenance of the Pinang Ranti Bus station is the lowest compared to other stations. It causes poor maintenance of the facilities with damages which directly affects the comfort and safety of users.